Fleuves, estuaires et cours : essai de généalogie scientifique d’un objet à la marge des sciences humaines et sociales - Olivier Sirost (VertigO)
This issue make a science audit provides from human and social sciences, which analyze PhD in France since 1972, and program research in estuary and rivers. This contribution try to understand interdisciplinarity in human and social sciences and their interest within aquatic topics and subjects. Further research using symbolism, social morphology, memory spaces, or scientific formation by exploration should be tracks for interdisciplinarity.